Pendidikan Karakter Dan Kearifan Lokal Pembentuk Sdm Unggul Dalam Era Globalisasi - Ni Wayan Silawati (STAHN Mpu Kuturan Singaraja, 2021)
Culture is often said to be a process or result of human creativity, taste, and initiative in an effort to answer the challenges of life from the natural surroundings. Culture will always be born accompanying the existence of the community itself. It is born and exists as an expression of self and the life of a human community that is being and will be experienced based on the context of society and its natural surroundings. Tradition is an important foundation in expressing oneself and life. Hefner (1985: 38), asserts, that the term adat itself has various regional uses. Indigenous diversity is a symbol of cultural differences, and most ethnic communities often justify adat as the source of their distinctive identity. Therefore, it becomes something that is quite firmly rooted in the personality system of the community in question. For example, areas in Bali that have unique traditions include Tabanan, with the nyentana cultural tradition, for example, indicating the characteristics and character of the Tabanan people who view gender equality as an essential right. Tenganan with the pandanus war tradition, is a hereditary tradition where each participant holds a pandanus and attacks his opponent by swiping the thorny pandanus on his opponent's body, especially on the back. Culture as a complex collection of customs has a tendency to defend itself. It can only reincarnate itself by influencing certain distinctive changes in the original and original structure of its members. This is what J. Dewey said in